Żydowskie wychowanie i żydowska tożsamość... - Zehavit Gross (Jesuit University Ignatianum in Krakow, 2017)
The author of the article analysed the profile of Jewish identity and education, indicating some essential problems and describing the way they are being tackled today. As far as Jewish identity is concerned, Z. Gross distinguished and depicted two separate standpoints, thus establishing two kinds of identity: substantive and constructive. She also described the diachronic and synchronic types of Jewish identity discourse, highlighting their implications for education. The educational system in Israel points to five fundamental historic events (the establishment of the Zionist Movement, the Holocaust, the establishment of the State of Israel, The Six Day War and the assassination of prime Minister Rabin) constituting a significant factor of Jewish Zionist education, addressing them in school curricula of particular subjects. Also, it is important to commemorate these events in educational processes in order to nurture the Jewish memory and strengthen Jewish national solidarity and identity despite the internal conflicts and fundamental reservations. Hence, the ability to compartmentalize and differentiate between consensus and conflict in the educational process is a salient feature of post-modern education. As to the synchronic discourse, the educational system in Israel requires transformation, since essentially no promoting forms have been undertaken, only some sporadic activities done by few teachers personally aware and committed to this problem. The contemporary educational system in Israel, according to Z. Gross, faces three closely interconnected cardinal problems in the ideological, social and administrative spheres. These difficulties result from the conflict between two Jewish civilizations and traditions: the traditional and the modern. As a consequence, dramatic transformations in Jewish identity and Jewish education are taking place. Therefore, these days the Israeli educational system needs to cerate a new, multicultural Jew, embodying the various identity conflicts that originated in historical and cultural processes. Such Jews are able to develop a dialectical approach towards the inherent conflicts, employing various identities as the basis of an identity capable of facing the special challenges of traditional society and adjusting itself gradually to ensure integration in the post-modern world.